The Comparison of the DASH and Mediterranean Diets in Reducing Cardiovascular Risk: A Comprehensive Review - Sobiś, Martyna; Miłek, Barbara; Janowiak, Julia; Janik, Natalia; Lenart, Julia; Górowska, Anna; Bogacka, Anna; Kiersznowska, Nina; Buchman, Małgorzata; Wadowska, Zuzanna (Quality in Sport, 2025)
Background: Cardiovascular diseases (CVDs) remain the leading cause of mortality worldwide and represent a major global health challenge (WHO, 2025). Compelling evidence indicates that dietary patterns substantially modulate cardiometabolic health and long-term cardiovascular outcomes. Among the most widely studied and recommended dietary models are the Mediterranean diet (MedDiet) and the Dietary Approaches to Stop Hypertension (DASH) diet. Aim: The aim of this review is to compare the effectiveness of the Mediterranean and DASH dietary patterns in reducing cardiovascular risk, improving cardiometabolic markers and preventing cardiovascular events. Material and methods: This narrative review was developed using 27 peer-reviewed sources, including randomized controlled trials, meta-analyses, systematic reviews and epidemiological reports published between 2011 and 2025. All findings presented derive strictly from validated scientific evidence. Results: The DASH diet provides the strongest and most consistent reductions in blood pressure, while the Mediterranean diet demonstrates broader and more potent effects on lipid metabolism, inflammation, metabolic regulation and long-term cardiovascular outcomes. Evidence from large randomized controlled trials and systematic reviews supports the Mediterranean diet as superior in long-term cardiovascular protection. Conclusions: Both dietary patterns exert significant cardiovascular benefits; however, the Mediterranean diet shows more comprehensive and sustained cardioprotective effects, whereas the DASH diet remains the optimal intervention for blood pressure reduction.